Teacher Strategies for Developing Fourth-Grade Students’ Critical Thinking Skills at SD Negeri 154511 Suga Suga - Jemrianti Habeahan; Olga Ananta Tarigan; Anna Mariani (Jurnal Pendidikan: Media, Strategi, dan Metode, 2025)
Critical thinking is an essential skill that enables elementary students to ask questions, analyze information, evaluate arguments, solve problems, and make reasoned decisions. However, critical thinking does not develop automatically; it requires deliberate instructional strategies, active learning opportunities, and teacher scaffolding. This study aims to describe teacher strategies for developing fourth-grade students’ critical thinking skills at SD Negeri 154511 Suga Suga in the 2023/2024 academic year. This study employed a descriptive qualitative design. Data were collected through classroom observation and semi-structured interviews with two teachers and two students. The data were analyzed through data reduction, data display, thematic interpretation, and conclusion drawing. The findings show that students’ critical thinking skills were still developing and were limited by several classroom conditions, including teacher-centered instruction, textbook-based explanation, limited student questioning, low confidence, and unequal student participation. Teachers attempted to support critical thinking through group discussion, open-ended questions, problem-solving tasks, project activities, quizzes, practical activities, feedback, and differentiated guidance. However, these strategies were not yet implemented consistently. The study concludes that teacher strategies for developing critical thinking need to be strengthened through more systematic questioning, student-centered learning, differentiated instruction, reflective discussion, and continuous feedback. The findings imply that elementary teachers should intentionally design learning activities that train students to ask, reason, explain, evaluate, and communicate ideas.